Pembuatan Sabun Cuci Piring Ramah Lingkungan dari Ekstrak Jeruk Nipis dan Daun Pandan Guna Meningkatkan Kesadaran Masyarakat akan Bahaya Bahan Kimia - Emi Sarnita; Yulia Windi Tanjung; Wahyu Andrean; Sara, Fitri; Dewi, Santi; Arisna, Cut; Feriandi, Nofi; Refta, Refta (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2024)
Community empowerment in making environmentally friendly dish soap from lime extract and pandan leaves is not just a service activity. It is a movement that aims to change people's consumption patterns, protect the environment, and improve economic welfare. Toxins are toxic and harmful substances produced in products. In addition, pandanus is also useful as a natural coloring material, but using it has a drawback, which is that the color is not very striking. The method used for community service activities in making environmentally friendly dish soap from lime extract and pandan leaves to increase public awareness of the dangers of chemicals is the demonstration method. The demonstration method is to demonstrate or show something in front of the public (Dewanti et al., 2020). Planning, implementation, elaboration and conclusion. The above stages provide guidance in implementing the extension program for making dish soap for the economically weak community in Tugan village, and ensure systematic and directed preparation, implementation, elaboration, and conclusions. According to the long-term impact evaluation, there is a possibility of an increase in the number of people interested in entrepreneurial training, opportunities for economic growth, and the emergence of a desire to participate in socio-economic empowerment. Overall, this community service program has produced good results and has been successful